Lower 123I-FP-CIT binding to the striatal dopamine transporter, but not to the extrastriatal serotonin transporter, in Parkinson's disease compared with dementia with Lewy bodies - Merijn Joling; Chris Vriend; Jessica J. van der Zande; Afina W. Lemstra; Odile A. van den Heuvel; Jan Booij; Henk W. Berendse (NeuroImage: Clinical, 2018)
In this retrospective cross-sectional study we compared 123I‑N‑ω‑fluoropropyl‑2β‑carbomethoxy‑3β‑(4‑iodophenyl)nortropane (123I-FP-CIT) binding to the striatal dopamine and the extrastriatal serotonin transporter (DAT and SERT, respectively) between Parkinson's disease (PD) and dementia with Lewy bodies (DLB) to gain more insight in the pathophysiology of the two diseases.We compared 123I-FP-CIT single photon emission computed tomography scans of, age-, gender matched patients with cognitive decline in same range of severity with PD (n = 53) or DLB (n = 53) using a regions of interest (ROIs) approach. We derived ROIs anatomically from individual magnetic resonance imaging brain scans. To corroborate the ROI findings, we performed additional whole-brain voxel-based analyses.In both ROI and voxel-based analyses, 123I-FP-CIT binding in PD patients was significantly lower in the bilateral posterior putamen than in DLB patients (left: F(1,103) = 18.363, P < 0.001, ω2 = 0.14; right: F(1,103) = 20.434, P < 0.001, ω2 = 0.15) (Pcorr < 0.033). Caudate/putamen ratios were also significantly lower in DLB than in PD (U(105) = 724.0, P < 0.001). Extrastriatal SERT binding showed no difference between PD and DLB.These results suggest similar involvement of serotonergic structures in the degenerative process in PD and DLB. Keywords: Parkinson's disease, Dementia with Lewy bodies, 123I-FP-CIT, SERT, DAT